IMPROVING ENGLISH LEARNING OUTCOMES THROUGHTWO STAY TWO STRAY LEARNING MODELAT SMPN BENTENG UTARA NO.4 KEPULAUAN SELAYAR - Kasmawati, Sri (Publikasi dan UKI Press UKI Toraja., 2022)
Based on the low learning outcomes of first grade students in English studies at SMPN Benteng Utara No.4 Kepulauan Selayar. The purpose of this study was to determine the level of effectiveness of the Two Stay Two Stray learning model as seen from the English studies learning outcomes of first grade students. The design of this study used the experimental method, with a sample of 24 students. The instruments used are observation and tests. There is a significant difference between English studies learning outcomes before and after the application of the Two Stay Two Stray learning model with the application of the lecture or conventional model. Those who scored 80-100 in the very good category were 13 students or 54.16%, while 6 students or 25% scored 66-79 in the good category, who scored 56-65 in the sufficient category from 5 students. or 20.84%. As well as students who get a score of 40-55 in the low category and no score <40 or less category at all. Therefore, the Two Stay Two Stray learning model is more effective than the conventional model